2004
DOI: 10.2337/diacare.27.11.2590
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Insulin Infusion Versus Multiple Daily Injections

Abstract: OBJECTIVE -Rapid-acting insulin analogs (insulin lispro and insulin aspart) have emerged as the meal insulin of choice in both multiple daily insulin injection (MDII) therapy and continuous subcutaneous insulin infusion (CSII) for type 1 diabetes. Thus, a comparison of efficacy between CSII and MDII should be undertaken only in studies that used rapid-acting analogs for both intensive regimens.RESEARCH DESIGN AND METHODS -We performed a pooled analysis of the randomized controlled trials that compared CSII and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
1
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(123 citation statements)
references
References 23 publications
11
98
1
13
Order By: Relevance
“…It should also be noted that the heterogeneity is not so much caused by qualitatively different results, but by quantitative differences. From these limitations it is clear that the results obtained from this meta-analysis have to be interpreted cautiously even though they are consistent with previously published meta-analyses [7,8,47,48].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It should also be noted that the heterogeneity is not so much caused by qualitatively different results, but by quantitative differences. From these limitations it is clear that the results obtained from this meta-analysis have to be interpreted cautiously even though they are consistent with previously published meta-analyses [7,8,47,48].…”
Section: Discussionsupporting
confidence: 83%
“…Recently published meta-analyses of studies comparing CSII and MDI treatment [7,8] demonstrated an improvement in glycaemic control with the use of CSII therapy in patients with type 1 diabetes mellitus. Currently, only a few reviews are available on adults, adolescents or younger children with type 1 and patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the reduction of HbA1c with CSII was not associated with an increased risk of severe hypoglycemia. This result is consistent with those of a previous meta-analysis on a patient-level data from three small trials [19], and of two larger meta-analyses which included trials applying CSII with RHI [1,2].…”
Section: Discussionsupporting
confidence: 82%
“…Several randomized clinical trials, usually on small samples of patients, comparing CSII using short-acting analogs and multiple daily injections (MDI) have been performed, reporting either a similar efficacy of the two approaches [6][7][8][9][10][11][12][13][14][15][16] or a superiority of CSII [17,18]. A meta-analysis on patient-level data from three clinical trials suggests an improvement of HbA1c with CSII (with lispro) as compared with MDI [19].…”
Section: Introductionmentioning
confidence: 99%
“…This approach provides increased flexibility in dosing and may improve quality of life in some patients. A meta-analysis of the studies evaluating the efficacy and safety of insulin pump therapy has found a modest advantage of this approach compared with multiple-dose insulin injection protocols (38,39). Currently, initiation of insulin pump therapy should be individualized, considering the patient's preferences, lifestyle, and self-care capabilities.…”
Section: Patients With Type 1 Diabetesmentioning
confidence: 99%